Telephone-delivered psychoeducational intervention for Hong Kong Chinese dementia caregivers: a single-blinded randomized controlled trial - Kwok, Timothy (Dove Medical Press, 2013)
PURPOSE: Many family caregivers of persons with dementia (PWD) are unable to participate in community center-based caregiver support services because of logistical constraints. This study evaluated the effectiveness of a telephone-delivered psychoeducational intervention for family caregivers of PWD in alleviating caregiver burden and enhancing caregiving self-efficacy. SUBJECTS AND METHODS: In a single-blinded randomized controlled trial, 38 family caregivers of PWD were randomly allocated into an intervention group or a control group. The intervention group received psychoeducation from a registered social worker over the phone for 12 sessions. Caregivers in the control group were given a DVD containing educational information about dementia caregiving. Outcomes of the intervention were measured by the Chinese versions of the Zarit Burden Interview and the Revised Scale for Caregiving Self-efficacy. Mann–Whitney U tests were used to compare the differences between the intervention and control groups. RESULTS: The level of burden of caregivers in the intervention group reduced significantly compared with caregivers in the control group. Caregivers in the intervention group also reported significantly more gain in self-efficacy in obtaining respite than the control group. CONCLUSION: A structured telephone intervention can benefit dementia caregivers in terms of self-efficacy and caregiving burden. The limitations of the research and recommendations for intervention are discussed.